Novel variation in the CEL gene causing impaired fasting glucose in a Chinese pediatric patient: case report and literature review - Su, Chang; Piao, Yurong; Chen, Congli; Wu, Di; Li, Rongmin; Sang, Yanmei (Frontiers in Endocrinology, 2026)
ObjectiveCEL-related Maturity-Onset Diabetes of the Young (CEL-MODY) is a rare form caused by carboxyl ester lipase (CEL) gene mutations. It is characterized by dysglycemia and pancreatic exocrine dysfunction. We described a case to highlights the heterogeneity of clinical manifestations of the CEL gene mutations in pediatric patients.Case presentationWe report a 12-year-old boy presenting with impaired fasting glucose. The patient reported no abdominal pain. Magnetic resonance imaging (MRI) of the pancreas revealed no evidence of pancreatic atrophy, fatty infiltration, or other abnormalities. Additionally, the fecal elastase level was within the normal range. Genetic analysis identified a novel heterozygous mutation in the CEL gene (c.1809dupC). The child exhibited only early-stage diabetes without concomitant pancreatic exocrine insufficiency, indicating a phenotypically mild form.ConclusionChildren with CEL gene mutations appear to exhibit significant phenotypic heterogeneity. It may be correlated with both the specific mutation type and age at disease onset. Thus, lifelong, systematic monitoring of pancreatic endocrine and exocrine function is clinically necessary.